Presence of listeria monocytogenes in pig carcasses in Lima, Peru - Barrientos H., Edy Waldo (2015)
The aim of this study was to determine the presence ofListeria monocytogenes in pig carcasses in Lima, Peru. Samples were collected from the the surface of 88 carcasses in a slaughterhouse. Samples were enriched with BLEB medium and PALCAM broth. The pathogen was identified using the in situ hybridization molecular technique. The 13.9 ± 6.1% of carcasses were positive to L. monocytogenes, possibly due to deficiencies in the application and control of good manufacturing practices and standard sanitary operations in the slaughterhouse.